METHODOLOGY FOR IMPLEMENTING SOFTWARE THAT IMPROVES INFORMATION TECHNOLOGY IN PRIMARY GRADES IN THE CONDITIONS OF DIGITALIZATION - Nazarov Ilkhomjon Usmanalievich (Bright Mind Publishing, 2025)
The article is devoted to the development and substantiation of methodological approaches to the effective implementation of innovative software solutions in the educational process of primary schools. The paper examines the issues of adapting content to the age characteristics of students, integrating software into the existing curriculum, as well as training teachers to work with new digital tools. The advantages of using advanced software for the development of algorithmic thinking, creative abilities and the formation of digital literacy of younger schoolchildren are analyzed. The research is aimed at improving the quality of information technology education in primary schools in the context of digitalization of education and the formation of students with the necessary competencies for successful adaptation to the modern information society.
Keywords: Implementation methodology, software, information technology, elementary grades, digitalization of education, digital resources, pedagogical technologies, digital literacy, content adaptation, effectiveness assessment, monitoring of results.